Culture of Mesenchymal Stem Cells Derived From the Infrapatellar Fat Pad Without Enzyme and Preliminary Study on the Repair of Articular Cartilage Defects in Rabbits - Fu, Qiwei; Zhou, Rong; Cao, Jia; Chen, Yi; Zhu, Jun; Zhou, Yiqin; Shao, Jiahua; Xin, Wei; Yuan, Shuai (Frontiers in Bioengineering and Biotechnology, 2022)
To evaluate the advantages of culturing patellar fat pad-derived mesenchymal stem cells (IPFP-SCs) without enzyme and its feasibility in repairing cartilage. The IPFP-SCs cultured by enzyme-free method were compared with the IPFP-SCs obtained by traditional enzyme digestion method in terms of cell proliferation ability, characterization and differentiation ability, and the differences in chondrogenic induction and differentiation were compared. Twenty-four New Zealand rabbits were randomly divided into four groups (n=6). After the articular cartilage defects were modeled, different preparations were injected into the joint cavity. The rats in the group A were injected with the mixture of IPFP-SCs and P-PRP separated without enzyme method, while those in the group B were injected with the mixture of IPFP-SCs and P-PRP separated with digestion method, while those in the group C were injected with SVF separated without enzyme method, and those in the group D were injected with normal saline. At 6 weeks and 12 weeks after operation, the cartilage repair of rabbit joint specimens was observed and evaluated by gross and histological staining, and the effects of different IPFP-SCs in the repair of cartilage defects were compared. The results showed that obtaining IPFP-SCs without enzyme method was less time-consuming than that with enzyme digestion method, and there was no significant difference in cell identification and differentiation potential between the two methods. However, the rate of obtaining primary cells was significantly lower than that with enzyme digestion method. IPFP-SCs showed good repair effect in rabbit cartilage defect model, and provided ideas and reference for the clinical application of stem cells in the repair of articular cartilage.